Avaliação dos efeitos da tarifa horária para consumidores rurais utilizando a geração fotovoltaica e/ou biomassa - Braida, Valeria (2020)
Low Voltage (LV) consumers are considered the most responsible for loading the electrical systems during peak hours by, increasing the expansion costs of the distribution system. To stimulate the efficient use of electricity, the National Electric Energy Agency (ANEEL) established a new tariff modality for low voltage consumers, the White Tariff, effective since January 2018. The White Tariff is an hourly rate with three different time schedules throughout a day. In addition to this new tariff modality, ANEEL established the conditions for access to distributed micro-generation and mini-generation since 2012 through the Normative Resolution (RN) No. 482, to encourage the inclusion of Distributed Generation (DG) in Low Voltage consumers. In this sense, the proposal of this dissertation is to present a study of the adhesion effects to the White Tariff for rural consumers using simultaneously photovoltaic and/or biomass energy sources, considering for this analysis the current energy tariffs and the typical load curves for each consumption range. The program Hybrid Optimization Model for Electric Renewables (HOMER) was used to perform the economic feasibility simulations and analysis and to make decisions in adhering or not to the White Tariff in conjunction with DG. Through this analysis, it was hoped to obtain an overview of the advantages and disadvantages that this new charging system compared to the conventional charging for rural consumers and the concessionaire, as well as the consumer's viability to join or not the renewable energy sources for insertion in distributed generation. Several configurations were evaluated under economic aspects and for different regions (Region South, Region Northeast and Northern Hemisphere). The results made it possible to identify which consumption ranges and regions would benefit the most through joining the White Tariff in conjunction with GD. It was concluded that out of the fifteen scenarios analyzed in only nine of these, the use of the Hourly Rate in conjunction with the DG became economically viable, with two scenarios for the South Region, two others for the Northeast Region and five scenarios for the Province of Ontario.